English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6 answers

Your answer is a start, but it's not complete. Use the difference of cubes formula to simplify more.

z^4-64z
= z(z^3 - 64)
= z(z^3 - 4^3)
= z(z - 4)(z^2 + 4z + 16)

2007-06-10 10:28:14 · answer #1 · answered by Mathematica 7 · 0 0

Hi

= z^4-64z
= z(z^3-64)
= z(z-4)(z^2+4z+16)

and the answer is
z(z-4)(z^2+4z+16) since it couldn't be factored anymore

2007-06-10 17:26:24 · answer #2 · answered by Croasis 3 · 0 0

No but here is how to do it
z^4-64z = z(z^3-64) = z(z-4)(z^2+4z+16)

2007-06-14 17:13:49 · answer #3 · answered by I ♥ Big Bang! 2 · 0 0

No. z^3-64 can be further factored as it is the difference between two cubes.

(a^3-b^3) = (a-b)(a^2+ab+b^2)
In your case a = z and b= 4

So (z^3-64) = (z-4)(z^2 + 4z + 16)

2007-06-10 17:38:23 · answer #4 · answered by ironduke8159 7 · 0 0

64 = 8*8 = 2^6

so factoring z we get

z(z^3 - 2^6)

let a=2^2

leaving you with z(z^3-a^3)

so solve for the cubic expression and substitute for a

Good luck!

2007-06-10 17:25:25 · answer #5 · answered by alrivera_1 4 · 0 0

z^4-64z

z(z^3-64)

z(z-4)(z^2+4z+16)

2007-06-10 17:26:56 · answer #6 · answered by Dave aka Spider Monkey 7 · 0 0

fedest.com, questions and answers